The Behavior of Superabsorbent Polymers (SAPs) in Cement Mixtures with Glass Powders as Supplementary Cementitious Materials - Farzanian, Khashayar (Materials (Basel), 2019)
The absorption and desorption of superabsorbent polymers (SAPs) in cement mixtures containing two different glass powders as supplementary cementitious materials are examined in this paper. Two SAPs with different chemical compositions were synthesized in-house and used in the experiments. SAP absorption was investigated directly through the mass change of SAPs in cement slurries, as well as indirectly using the flow test. Scanning electron microscopy was used to monitor the desorption of SAPs using samples prepared with freeze-drying. Hydration and setting time were evaluated to explain the desorption behavior of SAPs. SAP absorption generally increased in pastes with glass powders. The desorption rate of SAPs in different pastes was shown to correlate with the onset of solid skeleton development in the pastes. The addition of SAPs reduced autogenous shrinkage in neat cement paste more than in pastes with glass powders.